Pengaruh Cash Ratio, Debt to Equity Ratio, dan Earning Per Share Terhadap Dividend Payout Ratio Pada Perusahaan LQ45 Yang Terdaftar di Bursa Efek Indonesia Periode 2012-2015 - Ferdinand Napitupulu; Afrina Afrina (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2020)
Dividend payout ratio shows the share of the profit distributed in dividends. Dividend payout ratio affects investment decisions that will be invested by investors. Therefore, dividend payout ratio must be considered carefully by the company. This research was conducted at LQ45 company which listed in Indonesia Stock Exchange.The objective of this research is to find out the influence of the current ratio, return on equity, sales growth, and dividend payout ratio towards stock price partially or simultaneously. The population used in this research is LQ45 company which have been registered at Indonesia Stock Exchange from 2012 to 2015, with purposive sampling technique obtained sample of 52 company.The data in this research is secondary data andhypothesis testing method using the analysis of the regression of multiple linear. The examination using the analysis of the regression of multiple linear concludes the equation as follows : Y= 0,155 + 0,062X1+ 0,252X2+ X3.The result of this research showed that partially, debt to equity ratio and earning per share has the significant influence towards dividend payout ratio, while cash ratio does not. Simultaneously, cash ratio, debt to equity ratio, and earning per share influence dividend payout ratio significantly.